A preliminary checklist of Ficus l. species in Kuantan, Pahang - Moulana, Badrol Azim; Shahari, Rozilawati; Che Amri, Che Nurul Aini; Shamsuddin, Muhd Syufihuddin; Nik Rusmadi, Nik Nadira Nazua (Zibeline International Publishing Sdn. Bhd., 2020)
Ficus is the largest genus in the Moraceae family, with more than 700 species worldwide. It was classified into a distinct genus based on the unique nature of its inflorescence. Until recently, there was no official record of the Ficus checklist in Kuantan, Pahang. Therefore, this study aims to develop the preliminary checklist of Ficus species in Kuantan Pahang. Plant samples were collected from selected areas of Kuantan. Plant samples were pressed, dried and mounted on a herbarium board and processed as specimen vouchers. Based on this study, 14 species of Ficus were recorded. The list of Ficus presented in this study could be used for future research and as a reference source for conservation activities.